2022
DOI: 10.3390/life12091376
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Anxiety, Coping, and Autonomic Function in Takotsubo Syndrome Long after the Acute Event

Abstract: Background: Anxiety and depressive disorders represent predisposing factors for the autonomic dysfunctions that characterize the acute phase of Takotsubo syndrome (TS). However, there is insufficient data on this relationship after the acute event. The present study aimed at evaluating the psychological and autonomic status of patients with a history of TS. Methods: Ten TS patients whose acute event occurred at least 1 year prior to the evaluation and nine healthy age- and sex-matched subjects were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…A larger proportion of TTS patients had psychiatric disorders and neurological diseases compared with ACS patients 35 . Another study corroborates that ACS patients were less often affected by psychological disorders compared with TTS patients 15 . Similarly, another study found a higher frequency of TDP patients with emotionally triggered TTS compared with patients who had had an MI 18 .…”
Section: Risk Factorsmentioning
confidence: 64%
See 4 more Smart Citations
“…A larger proportion of TTS patients had psychiatric disorders and neurological diseases compared with ACS patients 35 . Another study corroborates that ACS patients were less often affected by psychological disorders compared with TTS patients 15 . Similarly, another study found a higher frequency of TDP patients with emotionally triggered TTS compared with patients who had had an MI 18 .…”
Section: Risk Factorsmentioning
confidence: 64%
“…35 Another study corroborates that ACS patients were less often affected by psychological disorders compared with TTS patients. 15 Similarly, another study found a higher frequency of TDP patients with emotionally triggered TTS compared with patients who had had an MI. 18 Ugo et al found that anxiety disorders were more prevalent in TTS patients, with depressive disorders being more prevalent in ACS patients.…”
Section: Takotsubo Syndrome Vs Acute Coronary Syndrome Pathophysiologymentioning
confidence: 93%
See 3 more Smart Citations